2011
DOI: 10.1016/j.jacc.2011.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic and Clinical Outcomes of MitraClip Therapy in Patients Not Amenable to Surgery

Abstract: MitraClip therapy improves clinical and echocardiographic outcomes at 1 year in about three-quarters of critically ill, elderly patients with moderate to severe MR not amenable to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 8 publications
11
63
0
4
Order By: Relevance
“…The exclusion criteria used were different from the commonly applied EVEREST criteria. 4 For degenerative MR, patients were considered unsuitable if (1) flail width was >25 mm and gap was >12 mm; (2) flail leaflets did not have secondary chordae support; (3) baseline mitral valve area (MVA) was <3.5 cm 2 and (4) there was excessive Barlow disease with multiple jets. For those with functional MR who had a central jet, patients were considered contraindicated for the procedure if (1) the gap between 2 leaflets was >3 mm; (2) there was a posteriororiented posterior mitral leaflet (PML) in a posterior wall aneurysm; and (3) there was a small baseline MVA <3.5 cm 2 with restrictive anterior mitral leaflet (AML).…”
Section: Mitraclip For Severe Mrmentioning
confidence: 99%
“…The exclusion criteria used were different from the commonly applied EVEREST criteria. 4 For degenerative MR, patients were considered unsuitable if (1) flail width was >25 mm and gap was >12 mm; (2) flail leaflets did not have secondary chordae support; (3) baseline mitral valve area (MVA) was <3.5 cm 2 and (4) there was excessive Barlow disease with multiple jets. For those with functional MR who had a central jet, patients were considered contraindicated for the procedure if (1) the gap between 2 leaflets was >3 mm; (2) there was a posteriororiented posterior mitral leaflet (PML) in a posterior wall aneurysm; and (3) there was a small baseline MVA <3.5 cm 2 with restrictive anterior mitral leaflet (AML).…”
Section: Mitraclip For Severe Mrmentioning
confidence: 99%
“…Subsequent nonrandomized studies of MitraClip have consistently shown clinically meaningful improvements in hemodynamic, echocardiographic, and quality of life measures, even with moderate residual MR present. [14][15][16] These findings imply that even modest reduction of MR is beneficial. However, it is not clear how much improvement in MR severity is necessary to result in reverse remodeling of the LV or LA.…”
mentioning
confidence: 97%
“…[16][17][18][19][20][21][22][23][24][25][26][27] A recent pooled analysis of 351 patients in the EVEREST II High Risk Registry and the REALISM (Real World Expanded Multi-center Study of the MitraClip System) Continued Access Study demonstrated an implantation success of 96%. 19 These patients were all considered high risk for surgery (estimated Society of Thoracic Surgeons score >12%).…”
Section: Evidence From Registriesmentioning
confidence: 99%